A descontinuidade causal como poética musical: modo de usar - Borges, Maryson José Siqueira (2022)
This work is the result of research into creative processes aiming to present the aesthetic principles that explain a compositional poetics based on and guided by an idea of causal discontinuity of language, forms, intuition and perception. The research is roughly divided into a reflective part and a practical part. The reflective, textual part basically comprises a set of critical parameters about what we call in the context of our poetic hypotheses “illusion of continuity” and about the basic formal requirements for taking advantage of the idea of causal discontinuity in some dimensions involved in the composition process. Namely, creative intuition, expression, musical perception, reception of works and formal inspiration. The practical part of the research, divided into two directions, seeks to set in motion some of these poetic assumptions derived from the criticism of the illusory continuity described in theoretical dialogues by applying the tetrad “axiom-contraintecombinatoria- clinamen” to the composition of a small series of original musical pieces and to the proposed metalinguistic reading of the thesis. This required reading mode seeks to emphasize the spiral and random apprehension of the elements that form the virtual and dynamic symbolic constellation of the parts continuously and repetitiously rearranged in the manner of an axiom, corresponding to the idea of founding discontinuity in the compositional poetics proposed. The constitutive elements of the virtual constellation named in the research as “inspiration architecture” are, briefly: (1) theoretical dialogues with Feyerabend, Jankelévitch, Jaynes, Mancuso, Albuquerque Jr., Benjamin and OuLiPo, (2) six musical compositions originally written for the research and the (3) formal discontinuity emulated in the proposed textual and graphic formatting of the thesis’ parts as a metalinguistic, modular, non-narrative “poetic installation” with volatile causality. An ideal approach to the work should therefore consider the reading of each of these parts both separately and as constituents of the axiomatic mobile that sustains the virtual discontinuity between the components of our musical poetics.